Bone erosion in rheumatoid arthritis: mechanisms, diagnosis and treatment - Schett, Georg (2012)
Bone erosion is a central feature of rheumatoid arthritis and is associated with disease severity and poor functional outcome. Erosion of periarticular cortical bone, the typical feature observed on plain radiographs in patients with rheumatoid arthritis, results from excessive local bone resorption and inadequate bone formation. The main triggers of articular bone erosion are synovitis, including the production of proinflammatory cytokines and receptor activator of nuclear factor κB ligand (RANKL), as well as antibodies directed against citrullinated proteins. Indeed, both cytokines and autoantibodies stimulate the differentiation of bone-resorbing osteoclasts, thereby stimulating local bone resorption. Although current antirheumatic therapy inhibits both bone erosion and inflammation, repair of existing bone lesions, albeit physiologically feasible, occurs rarely. Lack of repair is due, at least in part, to active suppression of bone formation by proinflammatory cytokines. This Review summarizes the substantial progress that has been made in understanding the pathophysiology of bone erosions and discusses the improvements in the diagnosis, monitoring and treatment of such lesions.